Disorders of higher gaze control. - Kennard, C (2011)
The neural centers in the cerebral hemispheres, both cortex and basal ganglia, involved in the generation of saccadic and smooth pursuit eye movements have been well delineated in terms of their location and function. For the generation of saccades these include the frontal eye fields, the supplementary eye field, and the intraparietal sulcus, and in the basal ganglia the caudate nucleus and the substantia nigra, pars compacta. The generation of pursuit eye movements involves the middle temporal (area V5) and medial superior temporal areas and the frontal eye field. These centers and their connections are disturbed not only in acute and chronic lesions such as cerebral infarction, but also in a wide variety of neurodegenerative diseases. In certain of these conditions, such as patients with cortical dementias and basal ganglia disorders, correct interpretation of the resulting eye movement abnormalities can contribute to differentiating between a range of differential diagnoses.